ANALISIS PENGARUH RETURN ON ASSETS, SALES GROWTH, STRUCTURE ASSETS, FIRM SIZE, DAN INVESTMENT OPPORTUNITY TERHADAP FINANCIAL LEVERAGE (studi perbandingan pada perusahaan manufaktur sektor aneka industri dan barang konsumsi yang terdaftar di BEI periode 20 - Pujiani, Suci; Prasetiono, Prasetiono (Diponegoro Journal of Management, 2012)
This research was conducted to test influence of the Return on Assets, Sales Growth, Structure Assets, Firm Size, and Investment Opportunity measure of firm to financial leverage. This research was compared two sectors of the manufacturing company which had gone public in Indonesian Stock Exchange periode 2008-2011. The intake techinque was purposive sampling methode and the obtained data were 15 manufacturing companies of miscellaneous industry sector and 25 of consumer goods sector. Data analysis using are the classic assumption test, multiple linear regression analysis, T test, F test, coefficient of determination, and the last is use of different test (chow test). Result of analysis in this research indicated that in miscellaneous industry companies, retun on assets, structure assets, and investment opportunity were significant. While in consumer goods companies, retun on assets and investment opportunity were accepted. To test for equality of coefficients from miscellaneous industry and consumer goods companies, this research used the different test chow test. Result of chow test showed the value of F calculate more than F table (2.26 >1.53) and this indicated there is difference between the determination of funding decision miscellaneous Industry sector companies and consumer goods sectors.